Demonstration of mRNA using digoxigenin labelled oligonucleotide probes for in situ hybridisation in formamide free conditions. Issue 2 (February 1993) - Thomas, G A; Davies, H G; Williams, E D
Abstract : The value of formamide for use in in situ hybridisation (ISH) for the detection of mRNA, using either single or multi probe cocktails of digoxigenin labelled oligoprobes, was investigated. Three peptides with cell specific localisation in three separate tissues--calcitonin in the thyroid, epidermal growth factor (EGF) in the submaxillary gland, and insulin in the pancreas were studied. In each case localisation was confined to the appropriate cell type, but in the presence of formamide higher concentrations of probe and a longer development time were required. The abolition of formamide from the protocol for ISH makes the technique safer, cheaper, faster and more suitable for routine diagnostic use.